2012
DOI: 10.1016/j.dcn.2011.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Emotional picture processing in children: An ERP study

Abstract: The late positive potential (LPP) reflects increased attention to emotional versus neutral stimuli in adults. To date, very few studies have examined the LPP in children, and whether it can be used to measure patterns of emotional processing that are related to dispositional mood characteristics, such as temperamental fear and anxiety. To examine this question, 39 typically-developing 5–7 year olds (M age in months = 75.27, SD = 5.83) passively viewed complex emotional and neutral pictures taken from the Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
97
4
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(119 citation statements)
references
References 51 publications
17
97
4
1
Order By: Relevance
“…That is, effects at frontal sites may be negative, but it is the positive deflection that is interpreted. This is consistent with the approach taken in Solomon et al (2012).…”
Section: Erp Data Analysissupporting
confidence: 91%
See 1 more Smart Citation
“…That is, effects at frontal sites may be negative, but it is the positive deflection that is interpreted. This is consistent with the approach taken in Solomon et al (2012).…”
Section: Erp Data Analysissupporting
confidence: 91%
“…Examination of the data was guided by similar investigations (Dawson et al, 2004;Dolcos and Cabeza, 2002;Hajcak and Dennis, 2009;Maratos and Rugg, 2001;Solomon et al, 2012). Based on the previous research and visual inspection of the ERP waveforms, we identified a sustained positive slow-wave consistent with the late positive potential (LPP) over all scalp sites.…”
Section: Erp Data Analysismentioning
confidence: 90%
“…That is, there is some evidence that abnormalities in the LPP may be observable among children at high risk for psychopathology prior to the onset of symptoms. For example, young children who exhibit behaviors consistent with fearful temperament styles have been shown to exhibit enhanced LPPs to unpleasant stimuli (Solomon, DeCicco, & Dennis, 2012) and blunted LPPs to emotional faces have been observed in children at high risk for depression (Kujawa, Hajcak et al, 2012). Thus, the LPP may provide a neural measure of patterns of emotional reactivity that contribute to the development of internalizing disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Cross-sectional research suggests the LPP may measure emotional processing styles that contribute to vulnerability for psychopathology. For example, offspring of parents with fear disorders (i.e., panic disorder, social anxiety disorder, and specific phobia) and children with fearful temperament showed enhanced LPPs to unpleasant stimuli (36; 37). In addition, blunted LPPs to emotional faces have been observed in youth at risk for depression based both on parental history of depression and temperament style (3739).…”
mentioning
confidence: 99%